WAIST CIRCUMFERENCE CUT-OFF POINTS OR BODY MASS INDEX FOR PREDICTING FAT MASS IN COLLEGE STUDENTS - RAMÍREZ-CALDERÓN, Bayner Julián; GONZALEZ-CORREA, Clara Helena; GONZÁLEZ-CORREA, Carlos Augusto (Brazilian Journal of Biometrics, 2020)
Obesity affects millions of people worldwide, becoming a public health problem with serious implications for human life quality. This is why low-cost prevention and diagnostic strategies that are accessible to the entire population are needed. Low-cost and easy-to-use strategies include the measurement of Body Mass Index (BMI) and measurement of waist circumference (WC). The objective was to determine whether the percentage of body fat in Colombian college students can be predicted through BMI or WC, establishing WC cutoff points. This was a descriptive cross-sectional study with a simple random sample. The study included 687 students aged 18-35 years old from both sexes. Anthropometric measures of weight, length, waist circumference at navel level and skin folds (bicipital, tricipital, subscapular and suprailiac) were obtained. The sensitivity and specificity of BMI and the waist circumference at navel level (WCN) were determined to predict the estimated percentage of body fat by measuring skin folds. The cutting points of the waist circumference for men and women were determined by drawing up a Receiver Operating Characteristic Curve (ROC). Greater sensitivity and specificity of WCN were found in comparison with BMI, to predict the percentage of body fat.